2003
DOI: 10.1143/jjap.42.477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonstoichiometry on the Deterioration of Eu2+-Doped Hexagonal Aluminate Phosphor for Plasma Display Applications

Abstract: The luminescence properties of blue phosphors 0.9BaOÁ0.1EuOÁMgOÁmAl 2 O 3 with m ¼ 3:5 to 8.0 were investigated for color plasma display panel (PDP) applications. The deterioration properties of the phosphors baked in air and irradiated under vacuum ultraviolet (VUV) rays were systematically studied with different alumina contents m. The results indicate that the phosphor with m ¼ 5:0 shows a relatively more stable color chromaticity after the baking process and VUV irradiation, whereas the phosphors with m ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…In PDP's plasma resonance, vacuum ultraviolet (VUV) radiation lines of Xe atoms at 147 nm and a molecular excimer Xe 2 at 172 nm are used for excitation of phosphors to emit visible luminescence in red, green and blue. All the three red, blue and green phosphors have shown degradation in luminescence intensity due to the thermal treatment of PDP manufacturing process and this remains a major problem for PDP phosphors [4][5][6][7]. Another challenge in PDP technology today is to improve the purity of red phosphor so as to obtain monochromatic red emission with good color coordinates [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PDP's plasma resonance, vacuum ultraviolet (VUV) radiation lines of Xe atoms at 147 nm and a molecular excimer Xe 2 at 172 nm are used for excitation of phosphors to emit visible luminescence in red, green and blue. All the three red, blue and green phosphors have shown degradation in luminescence intensity due to the thermal treatment of PDP manufacturing process and this remains a major problem for PDP phosphors [4][5][6][7]. Another challenge in PDP technology today is to improve the purity of red phosphor so as to obtain monochromatic red emission with good color coordinates [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge in PDP technology today is to improve the purity of red phosphor so as to obtain monochromatic red emission with good color coordinates [8,9]. Commercially used (Y,Gd)BO 3 4 Al 2 O 9 (x = 0.01 ≤ x ≤0.50). The powders were mechanically ground with 10 mole% H 3 BO 3 (99.9%) as flux in a mortar pestle, packed in an alumina crucible and subjected to two stage calcinations and sintering process between 700 and 1300°C in air atmosphere for 2-10 hours.…”
Section: Introductionmentioning
confidence: 99%
“…VUV damage may result from a radiation-induced change in the oxidation state of Eu, from migration of ions in the Ba-O plane of the host, or from the formation of some other electronic defects. Many methods have been proposed for improving the stability of BAM, ranging from modest compositional variations [5][6][7] to the introduction of trivalent ions into the host lattice [8,9]. However, none of these approaches has led to dramatic improvements in the stability of the phosphor, and many questions remain about the fundamental nature of these degradation phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…5. Zhang et al [23] also indicated that the highly crystallized BaMgAl 10 O 17 :Eu 2+ are resistance to the deterioration of the luminescence during baking process. This is consistent with phosphors under VUV damage [23,24].…”
Section: Xrd and Photoluminescence Analysismentioning
confidence: 99%
“…Zhang et al [23] also indicated that the highly crystallized BaMgAl 10 O 17 :Eu 2+ are resistance to the deterioration of the luminescence during baking process. This is consistent with phosphors under VUV damage [23,24]. They proved that improvement in the crystallization of BAM phosphor would not only enhance its emission efficiency but also decrease the deterioration during VUV irradiation.…”
Section: Xrd and Photoluminescence Analysismentioning
confidence: 99%